Semi - automated software requirement specification (SRS) document generator: The guideline to novice system analyst - Siti Nur Fathin Najwa, Mustaffa; Jamaludin, Sallim; Rozlina, Mohamed (IEEE, 2021)
Studies have emphasized that software requirements act as skeleton foundation of the digital project. This would help in the basis of detailed-design, development, test apps and maintenance. The Software Requirement Specifications (SRS) reflect functional and technical requirements that being used for the design and development process. There is, in any case, no impressive research between duplication requirement information and automated requirement tools to summed up issues in producing quality SRS documentation during requirement engineering phases. Issues such duplicate or redundant textual requirement information need to be heads up. This study is to investigate the quality of SRS document and factors of common problems during requirement engineering phases specially to solve the redundant and duplicate textual, analyze on how SRS is generated and the challenge on using requirement tools. The requirement may be missing, questionable, conflicting, unimplementable such the factor of project constraints. Thus, using semi-automated tool on generate SRS document can help in terms of feasible, relevant, clear, comprehensive, and accepted by all stakeholders as the deliverables. This is part of involvement in development process. Through evaluation and comparison with existing tool, the rule and guideline are adopted for this study with a proposed methodology. It purposely to deduce the necessity for examining the quality of SRS and an approach for evaluating the quality of the requirements in projects. As project more innovative, complex, and multi-disciplinary, it is essential to define and ensure the quality of the requirements at the preliminary stages. The findings of this study will distribute as guidelines for System Analyst as a factor of project success.